SILICON MANGANESE LIGHT SENSORS IN OPTICAL SENSING TECHNOLOGY - Mamarasulov Qudratbek Shuxratbek o‘g‘li; Boltaboyeva Xolidaxon G‘anijon qizi (Лучшие интеллектуальные исследования, 2024)
Silicon manganese light sensors, a recent breakthrough in optical sensing technology, have emerged as a promising solution for precise and reliable light detection. These sensors, based on the unique properties of silicon manganese (SiMn), exhibit enhanced sensitivity, a wide dynamic range, fast response times, and temperature stability. This article provides an overview of silicon manganese light sensors, highlighting their characteristics and advantages. The versatile nature of these sensors enables their application in various industries, including automotive, consumer electronics, industrial automation, and medical devices. Silicon manganese light sensors offer improved performance, cost-effectiveness, and versatility, making them a valuable addition to the field of optical sensing technology.